Examining knowledge translation in blood donor research: A review of vasovagal reaction literature. Issue 6 (2nd April 2021) - Thijsen, Amanda; Masser, Barbara; Davison, Tanya E.; Kruse, Sarah P.; Williamson, Anna
Abstract: Background: Knowledge translation focuses on the transfer of research findings into policy and practice. To provide insight into the state of knowledge translation in blood donor research, we undertook a rapid review of a key research area in the field with high potential for translation, vasovagal reactions (VVRs). We examined the number and nature of VVR‐related studies to determine the availability of research evidence, and mapped the included articles along the research‐to‐practice trajectory using the Knowledge to Action framework. Study Design and Methods: PubMed, PsycINFO, CINAHL, and EMBASE were searched for peer‐reviewed journal articles from inception to October 2019 using the terms blood don* AND vasovagal OR faint* OR syncope. Results: A total of 176 articles met our inclusion criteria. Studies relating to VVRs increased substantially from 1942 to 2019, with 84% published in the last 20 years. Articles were predominately observation (non‐intervention) studies (117; 66%), followed by intervention (knowledge inquiry) studies (31; 18%) and review (knowledge synthesis) studies (20; 11%). The evidence from intervention research was limited, with 14 strategies tested in 31 studies and often by the same research groups. Only 5 (3%) implementation and evaluation studies were found; all focused on evaluating the effects of a newly introduced intervention on VVR rates through uncontrolled or cross‐sectional study designs. Discussion: VVR research is in the early stages of knowledge translation. More intervention research is needed to provide a robust evidence base as well as more published implementation research to share knowledge of translating research into policy and practice.